Friction stir welding of AISI-316L steel pipes: Mechanical and metallurgical characterization of the joint. (December 2022) - Gain, Suresh; Sanyal, Dipankar; Acharyya, Sanjib Kumar; Das, Suman Kalyan
The present work attempts to develop a procedure for friction stir welding (FSW) of AISI-316L pipes. These pipes find applications across power, marine, food and chemical industries. Initially, welding is carried out in position control mode by setting parameters viz. spindle speed (RPM), transverse speed/feed rate (mm/min) and tool depth (mm) to get an idea about the welding process and to assess the effect of these parameters on the weldment. Based on the weld quality and the data recorded during the welding process, further welding is carried out in force control mode of the FSW setup. The welded joint at 300 rpm spindle speed and 35 kN force display greater strength (around 94%) compared to the base metal. The hardness of stir zone (SZ) as well as heat affected zone (HAZ) in welded samples was significantly higher compared to the base metal. The microstructural characterization revealed fine austenitic grain structures in SZ due to discontinuous dynamic recrystallization. In general, the weld is found to be consistent and the data obtained could be employed to produce high quality pipe welds.